PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (Survei pada Konsumen Produk Bolu CV Yaki Tiga Putri) - Derisna Febia Utami; Arga Sutrisna; Suci Putri Lestari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
The reseach aim to determine the partial and simultaneous influence of the promotion and brand image to the purchasing decision product yaki bread of tasikmalaya city. The methods used in this study is a quantitative methods with a survey.analysis of the data in this study used SPSS Version 26 software. The result showed that the simultaneous promotion and brand image had a significant role in the consumer purchasing decision yaki bread. Partially, the promotion has significant effect on the consumer purchasing decision yaki bread. Partially, the brand image has significant effect on the the consumer purchasing decision of yaki bread.